2023
DOI: 10.1038/s41467-023-36968-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication initiation factor RECQ4 possesses a role in antagonizing DNA replication initiation

Abstract: Deletion of the conserved C-terminus of the Rothmund-Thomson syndrome helicase RECQ4 is highly tumorigenic. However, while the RECQ4 N-terminus is known to facilitate DNA replication initiation, the function of its C-terminus remains unclear. Using an unbiased proteomic approach, we identify an interaction between the RECQ4 N-terminus and the anaphase-promoting complex/cyclosome (APC/C) on human chromatin. We further show that this interaction stabilizes APC/C co-activator CDH1 and enhances APC/C-dependent deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Similar cellular phenotypes were observed in cells with mutations in the ANAPC1 40 which causes RTS Type I whereas RTS Type II is caused by a mutation in the RECQ4 gene. Their possible mechanistic relationship is suggested by the work depicting direct interaction between APC1 and RECQ4 41 . Our findings of accumulation of UFBs in RTS-derived cells RECQ4/MUS81 inactivation support this, as well as random chromosome loss or gain, chromosomal aberrations, and enhanced telomere fragility 26 observed in fibroblasts derived from RTS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar cellular phenotypes were observed in cells with mutations in the ANAPC1 40 which causes RTS Type I whereas RTS Type II is caused by a mutation in the RECQ4 gene. Their possible mechanistic relationship is suggested by the work depicting direct interaction between APC1 and RECQ4 41 . Our findings of accumulation of UFBs in RTS-derived cells RECQ4/MUS81 inactivation support this, as well as random chromosome loss or gain, chromosomal aberrations, and enhanced telomere fragility 26 observed in fibroblasts derived from RTS patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some evidence indicates that RECQL4 protein levels are regulated during the cell cycle, and that the APC/C may promote RECQL4 degradation by the proteasome during the transition from mitosis to G1 (Ajeawung et al, 2019). In agreement with some form of cross-regulation between APC/C and RECQL4, the APC/C has recently been shown to interact with and regulate RECQL4 activity during the G1/S transition (Xu et al, 2023). Similarly, a quick search of the U12DB database (Genome Bioinformatics Research Lab, 2023) identified a U12-type intron in DNA2, suggesting that CRIPT may promote adequate splicing of the DNA2 transcript.…”
Section: Criptmentioning
confidence: 93%